Solid electrolyte, solid electrolyte layer and solid electrolyte battery

A solid electrolyte battery with improved ionic conductivity is achieved by using a compound of alkali metals and specific metallic elements, addressing the discharge capacity limitations of conventional batteries.

JP7608340B2Active Publication Date: 2025-01-06TDK CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021537680
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-07
Filing Date
2020-07-20
Publication Date
2025-01-06
Estimated Expiration
2040-07-20

Smart Images

  • Figure 0007608340000009
    Figure 0007608340000009
  • Figure 0007608340000001
    Figure 0007608340000001
  • Figure 0007608340000002
    Figure 0007608340000002
Patent Text Reader

Abstract

A solid electrolyte formed from a compound configured from an alkali metal, one or more monovalent to hexavalent metal elements or metalloid elements, an element in group 17 of the Periodic Table, and an element in group 16 of the Periodic Table.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte, a solid electrolyte layer, and a solid electrolyte battery. This application claims priority based on Japanese Patent Application No. 2019-145665 filed in Japan on August 7, 2019, the content of which is incorporated herein by reference.

Background Art

[0002] In recent years, the development of electronics technology has been remarkable, and mobile electronic devices have been made smaller, lighter, thinner, and more multifunctional. Along with this, there is a strong demand for batteries that power electronic devices to be smaller, lighter, and more reliable. For this reason, solid electrolyte batteries using solid electrolytes as electrolytes have attracted attention. As solid electrolytes, oxide-based solid electrolytes, sulfide-based solid electrolytes, complex hydride-based solid electrolytes (such as LiBH4), etc. are known.

[0003] Patent Document 1 discloses a solid electrolyte secondary battery having a positive electrode including a positive electrode layer containing a positive electrode active material containing an Li element and a positive electrode current collector, a negative electrode including a negative electrode layer containing a negative electrode active material and a negative electrode current collector, and a solid electrolyte composed of a compound represented by the following general formula, sandwiched between the positive electrode layer and the negative electrode layer. Li 3-2X M X In 1-Y M´ Y L 6-Z L´ Z (In the formula, M and M´ are metal elements, and L and L´ are halogen elements. Also, X, Y, and Z independently satisfy 0 ≦ X < 1.5, 0 ≦ Y < 1, and 0 ≦ Z ≦ 6.)

[0004] Patent Document 2 discloses a solid electrolyte material represented by the following compositional formula (1). Li 6-3Z Y Z X6 ··· Formula (1) Here, 0 < Z < 2 is satisfied, and X is Cl or Br. Moreover, Patent Document 2 describes a battery in which at least one of the negative electrode and the positive electrode contains the above-mentioned solid electrolyte material.

[0005] Patent Document 3 discloses a solid electrolyte battery including an electrode active material layer including an active material, a first solid electrolyte material in contact with the active material, which has an anion component different from that of the active material and is a single-phase mixed electron-ion conductor, and a second solid electrolyte material in contact with the first solid electrolyte material, which has the same anion component as the first solid electrolyte material and is an ion conductor without electronic conductivity. Patent Document 3 also discloses a solid electrolyte battery including a first solid electrolyte material having a Li2ZrS3 peak at 2θ=34.2°±0.5° in an X-ray diffraction measurement using CuKα radiation, and a diffraction intensity of the Li2ZrS3 peak at 2θ=34.2°±0.5° as I A The diffraction intensity of the ZrO2 peak at 2θ = 31.4° ± 0.5° is I B In this case, I B / I A It is disclosed that the value is 0.1 or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2006-244734 A [Patent Document 2] International Publication No. 2018 / 025582 [Patent Document 3] JP 2013-257992 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in conventional solid electrolyte batteries, the ionic conductivity of the solid electrolyte used in the solid electrolyte layer is insufficient, and therefore the conventional solid electrolyte batteries are unable to provide sufficient discharge capacity. The present invention has been made in view of the above problems, and has an object to provide a solid electrolyte having high ionic conductivity. Another object of the present invention is to provide a solid electrolyte layer having the above solid electrolyte, and a solid electrolyte battery having the same and having a large discharge capacity. [Means for solving the problem]

[0008] The present inventors have conducted extensive research in order to solve the above problems. As a result, the present inventors discovered that a compound composed of an alkali metal, at least one metal element or metalloid element having a valence of monovalent to hexavalent, and an element of Group 17 of the periodic table can be used as the solid electrolyte, and thus arrived at the present invention. That is, the present invention relates to the following inventions.

[0009] [1] An alkali metal, At least one metal element having a valence of 1 to 6; The elements of group 17 of the periodic table, It is composed of elements in group 16 of the periodic table, A solid electrolyte comprising a compound represented by the following formula (1): A 2+a E 1-b+α G b D c X d (1)

[0010] (In formula (1), A is an element selected from the group consisting of Li, K, and Na. E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. D is at least one element selected from the group consisting of O, Se, and Te. X is at least one element selected from the group consisting of F, Cl, Br, and I. a is -2b when G is a hexavalent element, -b when G is a pentavalent element, 0 when G is a tetravalent element or when G is not included, b when G is a trivalent element, 2b when G is a divalent element, and 3b when G is a monovalent element. b is 0 to 0.5. α is -0.3 to 0.3. c is 0.01 to 3. d is 0.1 to 6.1.

[0011] [2] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a monovalent element. [3] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a divalent element. [4] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a trivalent element.

[0012] [5] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a tetravalent element. [6] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a pentavalent element. [7] The solid electrolyte according to [1], wherein in the compound represented by formula (1), G is a hexavalent element.

[0013] [8] The solid electrolyte according to any one of [1] to [7], wherein in the compound represented by formula (1), X is F. [9] The solid electrolyte according to any one of [1] to [7], wherein in the compound represented by formula (1), X is Cl.

[10] The solid electrolyte according to any one of [1] to [7], wherein in the compound represented by formula (1), X is Br.

[11] The solid electrolyte according to any one of [1] to [7], wherein in the compound represented by formula (1), X is I.

[0014]

[12] The solid electrolyte according to any one of [1] to

[11] , wherein in the compound represented by formula (1), D is O.

[13] The solid electrolyte according to any one of [1] to

[11] , wherein in the compound represented by formula (1), D is Se.

[14] The solid electrolyte according to any one of [1] to

[11] , wherein in the compound represented by formula (1), D is Te.

[0015]

[15] The solid electrolyte according to [1], wherein in the compound represented by formula (1), A is Li, E is Zr, D is O, and X is Cl.

[16] The solid electrolyte according to [1], wherein in the compound represented by formula (1), A is Li, E is Zr, D is O, and X is I.

[0016]

[17] A2O, where A is an element selected from the group consisting of Li, K, and Na; AX (A is an element selected from the group consisting of Li, K, and Na. X is at least one element selected from the group consisting of F, Cl, Br, and I), EO2 (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn); EX4 (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. X is at least one selected from the group consisting of F, Cl, Br, and I), GO n(G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. n is 0.5 when G is a monovalent element, 1 when G is a divalent element, 1.5 when G is a trivalent element, 2 when G is a tetravalent element, 2.5 when G is a pentavalent element, and 3 when G is a hexavalent element). The solid electrolyte according to any of [1] to

[16] , comprising 0.1 to 1.0 mass % of at least one compound selected from the group consisting of:

[18] A solid electrolyte layer comprising the solid electrolyte according to any one of [1] to

[17] .

[19] A battery comprising a solid electrolyte layer, a positive electrode, and a negative electrode; A solid electrolyte battery in which at least one selected from the solid electrolyte layer, the positive electrode, and the negative electrode contains the solid electrolyte according to any one of [1] to

[17] .

[20] A solid electrolyte battery comprising a solid electrolyte layer, a positive electrode, and a negative electrode, the solid electrolyte layer containing the solid electrolyte according to any one of [1] to

[17] . Effect of the Invention

[0017] According to the present invention, a solid electrolyte having high ionic conductivity can be provided. In addition, the solid electrolyte layer of the present invention contains the solid electrolyte having high ionic conductivity. Therefore, a solid electrolyte battery including the solid electrolyte layer of the present invention has low internal resistance and high discharge capacity. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic cross-sectional view of a solid electrolyte battery according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The solid electrolyte, the solid electrolyte layer, and the solid electrolyte battery of the present invention will be described in detail below. [Solid electrolyte] The solid electrolyte of this embodiment is made of a compound composed of an alkali metal, at least one type of monovalent to hexavalent metal element or metalloid element, an element of Group 17 of the periodic table, and an element of Group 16 of the periodic table.

[0020] The solid electrolyte of this embodiment may be in the form of a powder (particles) made of the above compound, or in the form of a sintered body obtained by sintering the powder made of the above compound. The solid electrolyte of this embodiment may also be in the form of a compact obtained by compressing and molding the powder, a compact obtained by molding a mixture of the powder and a binder, or a coating film formed by applying a coating material containing the powder, a binder, and a solvent and then heating to remove the solvent.

[0021] The solid electrolyte of this embodiment is made of a compound represented by the following formula (1). A 2+a E 1-b+α G b D c X d (1) (In formula (1), A is an element selected from the group consisting of Li, K, and Na. E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. D is at least one element selected from the group consisting of O, Se, and Te. X is at least one element selected from the group consisting of F, Cl, Br, and I. a is -2b when G is a hexavalent element, -b when G is a pentavalent element, 0 when G is a tetravalent element or when G is not included, b when G is a trivalent element, 2b when G is a divalent element, and 3b when G is a monovalent element. b is 0 to 0.5. α is -0.3 to 0.3. c is 0.01 to 3. d is 0.1 to 6.1.

[0022] In the compound represented by formula (1), A is an element selected from the group consisting of Li, K and Na. A is preferably Li.

[0023] In the compound represented by formula (1), a is -2b when G is a hexavalent element, -b when G is a pentavalent element, 0 when G is a tetravalent element or when G is not included, b when G is a trivalent element, 2b when G is a divalent element, and 3b when G is a monovalent element. In the compound represented by formula (1), a is the above-mentioned numerical value determined by the valence of G, so that the content of A is appropriate, and a solid electrolyte with high ionic conductivity is obtained.

[0024] In the compound represented by formula (1), E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. E preferably contains Zr and / or Hf, and is particularly preferably Zr, in order to provide a solid electrolyte with high ionic conductivity.

[0025] In the compound represented by formula (1), G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W.

[0026] In the compound represented by formula (1), G may be a monovalent element selected from Au and Cs among those mentioned above. In the compound represented by formula (1), G may be a divalent element selected from the group consisting of Mg, Ca, Ba, Cu, Sn, Pb and Sr.

[0027] In the compound represented by formula (1), G may be a trivalent element selected from B, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Bi, In, and Sb. When G is trivalent, G is preferably Y because it becomes a solid electrolyte with high ionic conductivity.

[0028] In the compound represented by formula (1), G may be any of the tetravalent elements Si or Sn. When G is tetravalent, it is preferable that G is Sn, since this results in a solid electrolyte with high ionic conductivity.

[0029] In the compound represented by formula (1), G may be a pentavalent element selected from Nb and Ta among the above. When G is pentavalent, G becomes a solid electrolyte with high ionic conductivity, so that Nb and / or Ta are preferable, and Ta is particularly preferable. In the compound represented by formula (1), G may be, among the above, a hexavalent element, W. When G is hexavalent, it is preferable that G is W, since this results in a solid electrolyte with high ionic conductivity.

[0030] In the compound represented by formula (1), b is 0 to 0.5, and G may not be included, but it is preferable that G is included in order to provide a solid electrolyte with high ionic conductivity. When the compound represented by formula (1) contains G, b is preferably 0.02 or more. Also, b is set to 0.5 or less so as to prevent a decrease in the ionic conductivity of the solid electrolyte caused by an excessive content of G. In the compound represented by formula (1), b is preferably 0.2 or less.

[0031] In the compound represented by formula (1), D is at least one element selected from the group consisting of O, Se, and Te. D particularly preferably contains O, since this results in a solid electrolyte with high ionic conductivity. In the compound represented by formula (1), when D is at least one element selected from the group consisting of O, Se, and Te, any of the above elements, which is a divalent anion, is present at the position where X, which is a monovalent anion, should be, and therefore the crystallinity of the compound is reduced. Therefore, the ionic conductivity is improved, which is preferable.

[0032] In the compound represented by formula (1), D is an essential element. In the compound represented by formula (1), c is 0.01 to 3, and preferably 0.3 to 2.0. Since c is 0.01 or more, the effect of improving ionic conductivity due to the inclusion of D is sufficiently obtained. c is set to 3 or less so that the ionic conductivity of the solid electrolyte is not reduced due to the content of D being too high.

[0033] In the compound represented by formula (1), X is at least one selected from the group consisting of F, Cl, Br, and I. X preferably contains Cl and / or I in order to provide a solid electrolyte with high ionic conductivity, and more preferably contains Cl in order to provide a solid electrolyte with high ionic conductivity.

[0034] In the compound represented by formula (1), it is preferable that X is F, since this results in a solid electrolyte having sufficiently high ionic conductivity and excellent oxidation resistance. In the compound represented by formula (1), it is preferable that X is Cl, since this results in a solid electrolyte having high ionic conductivity and a good balance between oxidation resistance and reduction resistance. In the compound represented by formula (1), it is preferable that X is Br, since this results in a solid electrolyte having sufficiently high ionic conductivity and a good balance between oxidation resistance and reduction resistance. In the compound represented by formula (1), it is preferable that X is I, since this results in a solid electrolyte with high ionic conductivity.

[0035] In the compound represented by formula (1), X is an essential element, and d is 0.1 to 6.1, preferably 2.0 to 5.4. Since d is 0.1 or more, the effect of improving ionic conductivity by including X is sufficiently obtained. In addition, since d is 6.1 or less, the ionic conductivity of the solid electrolyte is not reduced due to the content of X being too high.

[0036] In the compound represented by formula (1), when the ratio of E to A is within an appropriate range, a solid electrolyte having high ionic conductivity is obtained, and therefore α is −0.3 to 0.3, preferably −0.2 to 0.2, and more preferably −0.1 to 0.1.

[0037] In the compound represented by formula (1), a compound in which A is Li, E is Zr, D is O, and X is Cl is preferable, since this compound has excellent resistance to reduction and provides a solid electrolyte with high ionic conductivity. In the compound represented by formula (1), since it becomes a solid electrolyte having excellent reduction resistance and high ionic conductivity, it may be a compound in which A is Li, E is Zr, D is O, and X is I.

[0038] In the compound represented by formula (1), the ratio of the ionic radius of X to the ionic radius per valence of E is preferably 7.0 to 15.0, and more preferably 8.0 to 13.0. The ionic radius per valence of E is the value obtained by dividing the ionic radius of E by the valence. When the ratio of the ionic radius of X to the ionic radius per valence of E is 7.0 or more, the ions of A in formula (1) are easily mobile, and a solid electrolyte with high ionic conductivity is obtained. When the ratio of the ionic radius of X to the ionic radius per valence of E is 15.0 or less, the thermal stability is improved, which is preferable.

[0039] The solid electrolyte of the present embodiment includes, in addition to the above compound, AO (A is an element selected from the group consisting of Li, K, and Na), AX (A is an element selected from the group consisting of Li, K, and Na. X is at least one element selected from the group consisting of F, Cl, Br, and I), EO (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn), EX (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. X is at least one element selected from the group consisting of F, Cl, Br, and I), and GO. n (G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. n is 0.5 when G is a monovalent element, 1 when G is a divalent element, 1.5 when G is a trivalent element, 2 when G is a tetravalent element, 2.5 when G is a pentavalent element, and 3 when G is a hexavalent element.)

[0040] Along with the above compounds, the above A2O, AX, EO2, EX4, and GO n A solid electrolyte containing 0.1 to 1.0 mass % of at least one compound selected from the group consisting of has even higher ionic conductivity. The reason for this is unclear, but is thought to be as follows. In such solid electrolytes, A2O, AX, EO2, EX4, GO n has a function of promoting ionic connection between particles of the above compound, which is presumably responsible for reducing grain boundary resistance between particles of the above compound and achieving high ionic conductivity for the solid electrolyte as a whole.

[0041] A2O, AX, EO2, EX4, GO contained in solid electrolyte nWhen the content of at least one compound selected from the group consisting of A2O, AX, EO2, EX4, GO is 0.1 mass% or more, n The effect of reducing the grain boundary resistance between the particles made of the above compounds by containing A2O, AX, EO2, EX4, GO n When the content of at least one compound selected from the group consisting of A2O, AX, EO2, EX4, GO is 1.0 mass% or less, n If the amount is too large, the solid electrolyte layer containing the solid electrolyte does not become hard, and a good interface that helps ionic connection between particles made of the compound does not become difficult to form.

[0042] (Method of manufacturing solid electrolyte) When the solid electrolyte of this embodiment is in a powder state, it can be produced by, for example, a method of mixing raw material powders containing predetermined elements in a predetermined molar ratio and causing a reaction. When the solid electrolyte of this embodiment is in a sintered state, it can be manufactured, for example, by the method shown below. First, raw material powders containing predetermined elements in a predetermined molar ratio are mixed. Next, the mixed raw material powders are molded into a predetermined shape and sintered in a vacuum or in an inert gas atmosphere. The halide raw material contained in the raw material powder is easily evaporated when the temperature is increased. For this reason, halogen gas may be made to coexist in the sintering atmosphere to compensate for the halogen. In addition, sintering may be performed by a hot press method using a mold with high sealing properties. In this case, since the mold has high sealing properties, the evaporation of the halide raw material due to sintering can be suppressed. By sintering in this manner, a solid electrolyte in a sintered state made of a compound having a predetermined composition is obtained.

[0043] The solid electrolyte of this embodiment is made of a compound including an alkali metal, at least one metal element or metalloid element having a valence of 1 to 6, an element of Group 17 of the periodic table, and an element of Group 16 of the periodic table, and therefore the solid electrolyte of this embodiment has high ionic conductivity.

[0044] In addition, since the compound in the solid electrolyte of the present embodiment is a compound represented by formula (1), it has high ionic conductivity. Although the details of the reason are unclear, it is considered as follows. In the compound represented by formula (1), E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. Zr 4+ (6 coordination), Hf 4+ (6 coordination), Ti 4+ (6 coordination), Sn 4+ The ionic radii of the (6-coordinate) elements are 0.72 Å, 0.71 Å, 0.605 Å, and 0.690 Å, respectively. The ionic radius of each element divided by the valence is, for example, Zr 4+ In the case of Hf, 0.72Å÷4=0.18Å. 4+ Then, it becomes 0.18 Å, and Ti 4+ Then, it is 0.15 Å, and Sn 4+ In the case of the compound represented by formula (1), X is at least one selected from the group consisting of F, Cl, Br, and I. - , Cl - , Br - , I - The ionic radii of are 1.33 Å, 1.81 Å, 1.96 Å, and 2.20 Å, respectively.

[0045] Thus, for example, Cl - The ratio of the ionic radius of Cl to the ionic radius of E per valence in formula (1) is - and Zr 4+ In the case of Cl, the result is 1.81÷0.18=10.1. - and Hf 4+ 10.2 for Cl - and Ti 4+ 12.0 for Cl - and Sn 4+ In the case of Cl, the value is 10.5. - The ionic radius of E and the tetravalent cation (Zr 4+ , Hf 4+ , Ti 4+ , Sn 4+The ratio to the ionic radius per valence is sufficiently large. Therefore, in the compound represented by formula (1), Cl - and the tetravalent cation E (Zr 4+ , Hf 4+ , Ti 4+ , Sn 4+ ) in formula (1) have a large free space between them, and Li + easily moves (conducts) through the interatomic gaps in the compound.

[0046] Also, in the compound represented by formula (1), D is at least one element selected from the group consisting of O, Se, and Te. Since D in formula (1) is an element with a weaker supplementary force for Li + compared to E in formula (1), for example, Li + moves more easily through the compound compared to a compound containing E instead of D in formula (1). Thus, the compound represented by formula (1) has a large ionic radius ratio as described above and contains D with a weak supplementary force for Li + , so Li + easily moves through the interatomic gaps in the compound. As a result, the compound represented by formula (1) is presumed to have high ionic conductivity.

[0047] On the other hand, for example, Patent Document 2 describes a solid electrolyte material represented by the composition formula Li 6-3Z Y Z X6 (where 0 < Z < 2 and X is Cl or Br). The ionic radius (6 - coordination) of Y 3+ , which is a constituent element of the solid electrolyte material described in Patent Document 2, is 0.9 Å. Therefore, the ratio of the ionic radius of Cl - to the ionic radius per valence of Y 3+ is 6.0. This value is smaller than the ratio of the ionic radius of Cl - to the ionic radius per valence of the tetravalent cation E (Zr 4+ , Hf 4+ , Ti 4+ , Sn 4+ ). Due to this difference, the compound represented by formula (1) has a higher Li than the solid electrolyte material described in Patent Document 2. + It is presumed that this allows for easy mobility and results in high ionic conductivity.

[0048] [Solid electrolyte battery] FIG. 1 is a schematic cross-sectional view of a solid electrolyte battery according to this embodiment. The solid electrolyte battery 10 shown in FIG. The solid electrolyte layer 3 is sandwiched between the positive electrode 1 and the negative electrode 2. The solid electrolyte layer 3 contains the above-mentioned solid electrolyte. The positive electrode 1 and the negative electrode 2 are connected to external terminals (not shown) and are electrically connected to the outside.

[0049] The solid electrolyte battery 10 is charged or discharged by the exchange of ions between the positive electrode 1 and the negative electrode 2 via the solid electrolyte layer 3. The solid electrolyte battery 10 may be a laminate in which the positive electrode 1, the negative electrode 2, and the solid electrolyte layer 3 are laminated, or may be a wound body in which the laminate is wound. The solid electrolyte battery is used, for example, in laminate batteries, square batteries, cylindrical batteries, coin batteries, button batteries, etc.

[0050] (positive electrode) As shown in FIG. 1, the positive electrode 1 has a positive electrode mixture layer 1B provided on a plate-shaped (foil-shaped) positive electrode current collector 1A. (Positive electrode current collector) The positive electrode current collector 1A may be made of any electronically conductive material that is resistant to oxidation during charging and is not easily corroded, such as metals such as aluminum, stainless steel, nickel, and titanium, or conductive resins. The positive electrode current collector 1A may be in the form of powder, foil, punching, or expandable. (Positive electrode mixture layer) The positive electrode mixture layer 1B contains a positive electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.

[0051] (Cathode active material) The positive electrode active material is not particularly limited as long as it can reversibly absorb and release, and insert and remove (intercalate and deintercalate) lithium ions, and any positive electrode active material used in known lithium ion secondary batteries can be used. Examples of the positive electrode active material include lithium-containing metal oxides and lithium-containing metal phosphates. Examples of lithium-containing metal oxides include lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese spinel (LiMn2O4), and lithium manganese oxide represented by the general formula: LiNi x Co y Mn z O2 (x+y+z=1), lithium vanadium compounds (LiVOPO4, Li3V2(PO4)3), olivine-type LiMPO4 (where M represents at least one selected from Co, Ni, Mn, and Fe), lithium titanate (Li4Ti5O 12 ) etc.

[0052] Lithium-free positive electrode active materials can also be used, such as non-lithium-containing metal oxides (MnO2, V2O5, etc.), non-lithium-containing metal sulfides (MoS2, etc.), and non-lithium-containing fluorides (FeF3, VF3, etc.). When using these positive electrode active materials not containing lithium, the negative electrode may be doped with lithium ions in advance, or a negative electrode containing lithium ions may be used.

[0053] (binder) In order to mutually bond the positive electrode active material, solid electrolyte, and conductive assistant constituting the positive electrode mixture layer 1B, and to adhere the positive electrode mixture layer 1B to the positive electrode current collector 1A, it is preferable that the positive electrode mixture layer 1B contains a binder. The properties required for the binder include oxidation resistance and good adhesiveness.

[0054] Examples of the binder used in the positive electrode mixture layer 1B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), polyethersulfone (PES), polyacrylic acid (PA) and its copolymer, metal ion crosslinked polyacrylic acid (PA) and its copolymer, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or a mixture thereof. Among these, it is particularly preferable to use PVDF as the binder.

[0055] The content of the solid electrolyte in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1 vol % to 50 vol %, and more preferably 5 vol % to 30 vol %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0056] The content of the binder in the positive electrode mixture layer 1B is not particularly limited, but is preferably 1% by mass to 15% by mass, more preferably 3% by mass to 5% by mass, based on the total mass of the positive electrode active material, solid electrolyte, conductive assistant, and binder. If the amount of binder is too small, it tends not to be possible to form a positive electrode 1 with sufficient adhesive strength. Conversely, if the amount of binder is too large, it tends to be difficult to obtain sufficient volume or mass energy density, since general binders are electrochemically inactive and do not contribute to discharge capacity.

[0057] (Conductive assistant) The conductive assistant is not particularly limited as long as it improves the electronic conductivity of the positive electrode mixture layer 1B, and any known conductive assistant can be used. Examples of the conductive assistant include carbon materials such as carbon black, graphite, carbon nanotubes, and graphene, metals such as aluminum, copper, nickel, stainless steel, iron, and amorphous metals, conductive oxides such as ITO, and mixtures thereof. The conductive assistant may be in the form of powder or fiber.

[0058] The content of the conductive assistant in the positive electrode mixture layer 1B is not particularly limited, but when the conductive assistant is added, it is usually preferably 0.5 mass % to 20 mass %, and more preferably 1 mass % to 5 mass %, based on the total mass of the positive electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0059] (Negative electrode) As shown in FIG. 1, the negative electrode 2 has a negative electrode mixture layer 2B provided on a negative electrode current collector 2A. (Negative electrode current collector) The negative electrode current collector 2A may be made of any conductive material, such as a metal such as copper, aluminum, nickel, stainless steel, or iron, or a conductive resin foil. The negative electrode current collector 2A may be in the form of a powder, a foil, a punched piece, or an expanded piece. (Negative electrode mixture layer) The negative electrode mixture layer 2B contains a negative electrode active material, and optionally contains a solid electrolyte, a binder, and a conductive assistant.

[0060] (Negative electrode active material) The negative electrode active material is not particularly limited as long as it can reversibly absorb and release lithium ions and insert and extract lithium ions, and any negative electrode active material used in known lithium ion secondary batteries can be used. Examples of the negative electrode active material include carbon materials such as natural graphite, artificial graphite, mesocarbon microbeads, mesocarbon fiber (MCF), cokes, glassy carbon, and organic compound sintered bodies; metals that can be combined with lithium, such as Si, SiOx, Sn, and aluminum; alloys of these; composite materials of these metals and carbon materials; and lithium titanate (Li4Ti5O 12 ), oxides such as SnO2, and metallic lithium.

[0061] (binder) In order to mutually bond the negative electrode active material, the solid electrolyte, and the conductive assistant constituting the negative electrode mixture layer 2B, and to adhere the negative electrode mixture layer 2B to the negative electrode current collector 2A, it is preferable that the negative electrode mixture layer 2B contains a binder. Required properties of the binder include reduction resistance and good adhesiveness. Examples of the binder used in the negative electrode mixture layer 2B include polyvinylidene fluoride (PVDF) or its copolymer, polytetrafluoroethylene (PTFE), polyamide (PA), polyimide (PI), polyamideimide (PAI), polybenzimidazole (PBI), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PA) and copolymers, metal ion crosslinked bodies of polyacrylic acid (PA) and copolymers, polypropylene (PP) grafted with maleic anhydride, polyethylene (PE) grafted with maleic anhydride, or mixtures thereof. Among these, it is preferable to use one or more types selected from SBR, CMC, and PVDF as the binder.

[0062] The content of the solid electrolyte in the negative electrode mixture layer 2B is not particularly limited, but is preferably 1 vol. % to 50 vol. %, and more preferably 5 vol. % to 30 vol. %, based on the total mass of the negative electrode active material, the solid electrolyte, the conductive assistant, and the binder.

[0063] The content of the binder in the negative electrode mixture layer 2B is not particularly limited, but is preferably 1% by mass to 15% by mass, and more preferably 1.5% by mass to 10% by mass, based on the total mass of the negative electrode active material, the conductive assistant, and the binder. If the amount of the binder is too small, it tends not to be possible to form a negative electrode 2 having sufficient adhesive strength. Conversely, if the amount of the binder is too large, the binder is generally electrochemically inactive and does not contribute to the discharge capacity, so that it tends to be difficult to obtain a sufficient volume or mass energy density.

[0064] (Conductive assistant) As the conductive assistant that may be contained in the negative electrode mixture layer 2B, the same conductive assistant as the above-mentioned conductive assistant that may be contained in the positive electrode mixture layer 1B, such as a carbon material, may be used.

[0065] The content of the conductive additive in the negative electrode mixture layer 2B is not particularly limited, but when a conductive additive is added, it is usually preferable that the content be 0.5% by mass to 20% by mass, and more preferably 1% by mass to 12% by mass, relative to the negative electrode active material.

[0066] (Exterior body) In the solid electrolyte battery 10 of this embodiment, a battery element consisting of a positive electrode 1, a solid electrolyte layer 3, and a negative electrode 2 is housed and sealed in an exterior body. The exterior body is not particularly limited as long as it can prevent the intrusion of moisture and the like from the outside to the inside. For example, the exterior body may be a bag-shaped metal laminate film made by coating both sides of a metal foil with a polymer film. Such an exterior body is sealed by heat sealing the opening. The metal foil forming the metal laminate film may be, for example, an aluminum foil, a stainless steel foil, etc. The polymer film disposed on the outside of the exterior body is preferably a polymer with a high melting point, such as polyethylene terephthalate (PET), polyamide, etc. The polymer film disposed on the inside of the exterior body is preferably, for example, polyethylene (PE), polypropylene (PP), etc.

[0067] (External terminal) A positive electrode terminal is electrically connected to the positive electrode 1 of the battery element, and a negative electrode terminal is electrically connected to the negative electrode 2. In this embodiment, the positive electrode terminal is electrically connected to the positive electrode current collector 1A, and the negative electrode terminal is electrically connected to the negative electrode current collector 2A. The connection portion between the positive electrode current collector or the negative electrode current collector and the external terminals (positive electrode terminal and negative electrode terminal) is disposed inside the exterior body. The external terminals may be made of a conductive material such as aluminum or nickel.

[0068] It is preferable that a film made of PE grafted with maleic anhydride (hereinafter sometimes referred to as "acid-modified PE") or PP grafted with maleic anhydride (hereinafter sometimes referred to as "acid-modified PP") is disposed between the exterior body and the external terminal. By heat sealing the portion where the film made of acid-modified PE or acid-modified PP is disposed, a solid electrolyte battery with good adhesion between the exterior body and the external terminal is obtained.

[0069] [Method of manufacturing solid electrolyte battery] Next, a method for manufacturing the solid electrolyte battery according to this embodiment will be described. First, the above-mentioned solid electrolyte is prepared to become the solid electrolyte layer 3 included in the solid electrolyte battery 10 of the present embodiment. In the present embodiment, a powdered solid electrolyte is used as the material for the solid electrolyte layer 3. The solid electrolyte layer 3 can be produced by a powder formation method. Also, for example, a paste containing a positive electrode active material is applied onto a positive electrode current collector 1A, and then dried to form a positive electrode mixture layer 1B, thereby producing a positive electrode 1. Also, for example, a paste containing a negative electrode active material is applied onto a negative electrode current collector 2A, and then dried to form a negative electrode mixture layer 2B, thereby producing a negative electrode 2.

[0070] Next, for example, a guide with a hole is placed on the positive electrode 1, and the guide is filled with a solid electrolyte. After that, the surface of the solid electrolyte is smoothed, and the negative electrode 2 is placed on top of the solid electrolyte. As a result, the solid electrolyte is sandwiched between the positive electrode 1 and the negative electrode 2. Then, pressure is applied to the positive electrode 1 and the negative electrode 2 to pressure-form the solid electrolyte. By pressure-forming, a laminate is obtained in which the positive electrode 1, the solid electrolyte layer 3, and the negative electrode 2 are layered in this order. Next, external terminals are welded to the positive electrode current collector of the positive electrode 1 and the negative electrode current collector of the negative electrode 2, which form the laminate, by a known method, to electrically connect the positive electrode current collector or the negative electrode current collector to the external terminal. Thereafter, the laminate connected to the external terminal is housed in an exterior body, and the opening of the exterior body is heat-sealed to seal it. Through the above steps, the solid electrolyte battery 10 of the present embodiment is obtained.

[0071] In the above-mentioned method for manufacturing the solid electrolyte battery 10, an example has been described in which a powdered solid electrolyte is used. However, a sintered solid electrolyte may also be used as the solid electrolyte. In this case, the solid electrolyte in a sintered state is sandwiched between the positive electrode 1 and the negative electrode 2, and pressure-molded to obtain a solid electrolyte battery 10 having a solid electrolyte layer 3.

[0072] The solid electrolyte layer 3 of this embodiment contains the solid electrolyte of this embodiment, which has high ion conductivity. Therefore, the solid electrolyte battery 10 of this embodiment, which includes the solid electrolyte layer 3 of this embodiment, has a small internal resistance and a large discharge capacity.

[0073] The embodiments of the present invention have been described above in detail with reference to the drawings. The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. EXAMPLES

[0074] ( Reference Examples 1 to 10, Example 11 ~ Example 79 and Comparative Example 1) A powder of raw materials containing the specified raw materials in the molar ratios shown in Tables 1 to 4 was mixed and reacted for 24 hours using a planetary ball mill at a rotation speed of 1 rpm, a revolution speed of 500 rpm, and the rotation direction and the revolution direction in the opposite directions to each other, to produce a powder of compounds having the compositions shown in Tables 5 to 8. Reference Examples 1 to 10, Example 11 The solid electrolyte of Example 79 was produced.

[0075] The composition of each solid electrolyte was determined by a method of analyzing each element except oxygen using an ICP (inductively coupled plasma atomic emission spectrometry) device (manufactured by Shimadzu Corporation). For solid electrolytes containing fluorine, the content of fluorine in the solid electrolyte was analyzed using an ion chromatography device (manufactured by Thermo Fisher Scientific Co., Ltd.). In addition, in Tables 5 to 8, the percentage of oxygen contained in each solid electrolyte is shown in the percentage of oxygen in the raw material powders shown in Tables 1 to 4. Note that, by conducting experiments in advance, it was confirmed that the percentage of oxygen contained in the solid electrolyte can be considered to be equivalent to the percentage of oxygen contained in the raw material powders.

[0076] In addition, the sealed container and balls for the planetary ball mill were made of zirconia. Therefore, zirconium originating from the sealed container and balls was mixed into the produced compound as contamination. It is known that the amount of zirconium contamination originating from the sealed container and balls is a certain constant amount. Tables 5 to 8 show the measured values ​​of the zirconium content in the compound.

[0077] (Example 80 to Example 84) The solid electrolyte (Li2ZrOCl4) prepared in Example 16 was mixed with 0.1 mass % each of Li2O, LiCl, ZrO2, ZrCl4, and CaO as additives to prepare a solid electrolyte.

[0078] Tables 1 to 4 show the raw materials used in each solid electrolyte and the raw material compounding ratio (molar ratio), the ionic radius of "X" when the composition of each solid electrolyte is applied to formula (1), and the ratio of the ionic radius of "X" to the ionic radius per valence of "E". In addition, in Tables 5 to 8, the composition of each solid electrolyte is indicated as "〇" if it satisfies the above formula (1), and indicated as "-" if it does not. Furthermore, Tables 5 to 8 show "A", "E", "G", "D", "valence of G", "X", "a", "b", "α", "c", and "d" when the composition of each solid electrolyte is applied to formula (1).

[0079] [Table 1]

[0080] [Table 2]

[0081] [Table 3]

[0082] [Table 4]

[0083] [Table 5]

[0084] [Table 6]

[0085] [Table 7]

[0086] [Table 8]

[0087] (Measurement of ionic conductivity) Reference Examples 1 to 10, Example 11 The solid electrolytes of Example 84 and Comparative Example 1 were each filled into a pressure molding die and pressure molded at a pressure of 373 MPa to obtain test specimens. More specifically, a resin holder with a diameter of 10 mm and an upper punch and a lower punch with a diameter of 9.99 mm were prepared. The upper and lower punches were made of die steel (SKD material). The lower punch was inserted into the resin holder and pressed from above. Reference Examples 1 to 10, Example 11 110 mg of the solid electrolyte of Example 84 and Comparative Example 1 was added. An upper punch was inserted on the solid electrolyte. The upper and lower punches were inserted into the resin holder, which is referred to as a set here. The set was placed on a press machine and molded at a pressure of 373 MPa. The set was removed from the press machine.

[0088] Two stainless steel disks and two Teflon disks, each with a diameter of 50 mm and a thickness of 5 mm, were prepared. The stainless steel disks and the Teflon disks had four screw holes. The stainless steel disks and the Teflon disks were placed on the top and bottom of the set, and the set was pressurized by passing screws through the four screw holes and tightening the screws. Specifically, a jig for measuring ionic conductivity was made by laminating a stainless steel disk / Teflon (registered trademark) disk / set / Teflon (registered trademark) disk / stainless steel disk in this order and tightening the screws. The upper and lower punches had screw holes on the sides for inserting screws. The upper and lower punches were inserted with screws to make terminals for measuring ionic conductivity.

[0089] Thereafter, the ionic conductivity of each test specimen housed in the set of ionic conductivity measurement jigs was measured. The ionic conductivity was measured by electrochemical impedance measurement using a potentiostat equipped with a frequency response analyzer. The measurement was performed under conditions of a frequency range of 7 MHz to 0.1 Hz, an amplitude of 10 mV, and a temperature of 30°C. The results are shown in Tables 5 to 8.

[0090] [Preparation of solid electrolyte battery] By the method shown below, Reference Examples 1 to 10, Example 11 Solid electrolyte batteries having solid electrolyte layers made of the solid electrolytes of Examples 1 to 84 and Comparative Example 1 were fabricated. The fabrication of the solid electrolyte batteries was carried out in a glove box with an argon atmosphere having a dew point of -70°C or less. In addition, a charge / discharge test was carried out by the method described below, and the discharge capacity was measured. First, lithium cobalt oxide (LiCoO2): Reference Examples 1 to 10, Example 11 The solid electrolyte and carbon black of each of Example 84 and Comparative Example 1 were weighed out so that the ratio was 81:16:3 parts by weight, and mixed in an agate mortar to prepare a positive electrode mixture. Reference Examples 1 to 10, Example 11 The solid electrolyte and carbon black from Example 84 and Comparative Example 1 were weighed out so that the ratio was 67:30:3 parts by weight, and mixed in an agate mortar to prepare a negative electrode mixture.

[0091] The lower punch is inserted into the resin holder, and the resin holder is Reference Examples 1 to 10, Example 11 110 mg of the solid electrolyte of Example 84 and Comparative Example 1 was added. An upper punch was inserted on top of the solid electrolyte. This set was placed in a press and molded at a pressure of 373 MPa. The set was removed from the press, and the upper punch was removed. 39 mg of positive electrode mixture was placed on top of the solid electrolyte (pellet-shaped) in the resin holder, an upper punch was inserted on top of it, the set was placed in a press machine, and molded at a pressure of 373 MPa. The set was then removed, turned upside down, and the lower punch was removed. 20 mg of negative electrode mixture was placed on top of the solid electrolyte (pellet), a lower punch was inserted on top of it, the set was placed in a press machine, and molded at a pressure of 373 MPa. In this way, a battery element consisting of a positive electrode, a solid electrolyte, and a negative electrode was fabricated in the resin holder. Screws were inserted into the screw holes on the sides of the upper and lower punches as terminals for charging and discharging.

[0092] An aluminum laminate material was prepared as an exterior body for enclosing the battery element. This is a laminate material made of PET (12) / Al (40) / PP (50). PET is polyethylene terephthalate, and PP is polypropylene. The thickness of each layer (unit: μm) is shown in parentheses. This aluminum laminate material was cut to A4 size and folded back in the middle of the long side so that the PP was on the inner surface.

[0093] An aluminum foil (width 4 mm, length 40 mm, thickness 100 μm) was prepared as the positive electrode terminal. A nickel foil (width 4 mm, length 40 mm, thickness 100 μm) was prepared as the negative electrode terminal. Acid-modified PP was wrapped around each of these external terminals (positive electrode terminal and negative electrode terminal) and thermally bonded to the exterior body. This was to improve the sealing between the external terminals and the exterior body.

[0094] A positive electrode terminal and a negative electrode terminal were placed in the middle of each of the two opposing sides of the folded aluminum laminate material so as to be sandwiched between the aluminum laminate material, and heat-sealed. Then, the set was inserted into an exterior body, and the screw on the side of the upper punch was connected to the positive electrode terminal inside the exterior body with a lead wire, thereby electrically connecting the positive electrode and the positive electrode terminal. Also, the screw on the side of the lower punch was connected to the negative electrode terminal inside the exterior body with a lead wire, thereby electrically connecting the negative electrode and the negative electrode terminal. Then, the opening of the exterior body was heat-sealed to form a solid electrolyte battery.

[0095] The charge and discharge tests were carried out in a thermostatic chamber at 25°C. The charge and discharge currents are expressed in C (C) rate notation hereafter. nC (mA) is the current at which the nominal capacity (mAh) can be charged and discharged at 1 / n (h). For example, for a battery with a nominal capacity of 70mAh, the current at 0.05C is 3.5mA (calculated as 70 x 0.05 = 3.5). Similarly, the current at 0.2C is 14mA, and the current at 2C is 140mA. Charging was performed at 0.2C up to 4.2V at constant current constant voltage (CCCV). Charging was completed when the current was 1 / 20C. Discharging was performed at 0.2C up to 3.0V. The results are shown in Tables 5 to 8.

[0096] As shown in Tables 5 to 8, Reference Examples 1 to 10, Example 11 The solid electrolytes of Example 84 to Comparative Example 1 all had sufficiently high ionic conductivity. Reference Examples 1 to 10, Example 11 The solid electrolyte batteries having the solid electrolyte layer made of the solid electrolyte of Example 84 to Comparative Example 1 all had sufficiently large discharge capacity as compared with the solid electrolyte of Comparative Example 1. [Explanation of symbols]

[0097] 1... positive electrode, 1A... positive electrode current collector, 1B... positive electrode mixture layer, 2... negative electrode, 2A... negative electrode current collector, 2B... negative electrode mixture layer, 3... solid electrolyte layer, 10... solid electrolyte battery.

Claims

1. An alkali metal, At least one metal element having a valence of 1 to 6; An element of group 17 of the periodic table; It is composed of elements from group 16 of the periodic table, A solid electrolyte comprising a compound represented by the following formula (1): A 2+a E 1-b+α G b D c X d ・・・(1) (In formula (1), A is an element selected from the group consisting of Li, K, and Na. E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Cu, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. D is at least one element selected from the group consisting of O, Se, and Te. X is at least one element selected from the group consisting of F, Cl, Br, and I. a is -2b when G is a hexavalent element, -b when G is a pentavalent element, 0 when G is a tetravalent element or when G is not included, b when G is a trivalent element, 2b when G is a divalent element, and 3b when G is a monovalent element. b is 0 to 0.

5. α is -0.3 to 0.

3. c is 0.01 to 3. d is 0.1 to 6.

1.

2. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a monovalent element.

3. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a divalent element.

4. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a trivalent element.

5. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a tetravalent element.

6. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a pentavalent element.

7. The solid electrolyte according to claim 1 , wherein in the compound represented by formula (1), G is a hexavalent element.

8. The solid electrolyte according to any one of claims 1 to 7, wherein in the compound represented by formula (1), X is F.

9. The solid electrolyte according to any one of claims 1 to 7, wherein in the compound represented by formula (1), X is Cl.

10. The solid electrolyte according to any one of claims 1 to 7, wherein in the compound represented by formula (1), X is Br.

11. The solid electrolyte according to any one of claims 1 to 7, wherein in the compound represented by formula (1), X is I.

12. The solid electrolyte according to any one of claims 1 to 11, wherein in the compound represented by formula (1), D is O.

13. The solid electrolyte according to any one of claims 1 to 11, wherein in the compound represented by formula (1), D is Se.

14. The solid electrolyte according to any one of claims 1 to 11, wherein in the compound represented by formula (1), D is Te.

15. 2. The solid electrolyte according to claim 1, wherein in the compound represented by formula (1), A is Li, E is Zr, D is O, and X is Cl.

16. 2. The solid electrolyte according to claim 1, wherein in the compound represented by formula (1), A is Li, E is Zr, D is O, and X is I.

17. A 2 O (A is an element selected from the group consisting of Li, K, and Na), AX (A is an element selected from the group consisting of Li, K, and Na. X is at least one element selected from the group consisting of F, Cl, Br, and I), E.O. 2 (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn), EX 4 (E is at least one tetravalent element selected from the group consisting of Zr, Hf, Ti, and Sn. X is at least one element selected from the group consisting of F, Cl, Br, and I.) GO n (G is at least one element selected from the group consisting of B, Si, Mg, Ca, Sr, Cs, Ba, Y, Al, Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Eu, Tm, Yb, Lu, Cu, Ag, Au, Pb, Bi, In, Sn, Sb, Nb, Ta, and W. n is 0.5 when G is a monovalent element, 1 when G is a divalent element, 1.5 when G is a trivalent element, 2 when G is a tetravalent element, 2.5 when G is a pentavalent element, and 3 when G is a hexavalent element.) The solid electrolyte according to any one of claims 1 to 16, comprising 0.1 to 1.0 mass% of at least one compound selected from the group consisting of.

18. A solid electrolyte layer comprising the solid electrolyte according to any one of claims 1 to 17.

19. A solid electrolyte layer, a positive electrode, and a negative electrode are provided. A solid electrolyte battery, wherein at least one selected from the solid electrolyte layer, the positive electrode, and the negative electrode contains the solid electrolyte according to any one of claims 1 to 17.

20. A solid electrolyte battery comprising a solid electrolyte layer, a positive electrode, and a negative electrode, the solid electrolyte layer containing the solid electrolyte according to any one of claims 1 to 17.

Citation Information

Patent Citations

  • All-solid lithium secondary battery

    JP2006244734A

  • All-solid battery and manufacturing method of all-solid battery

    JP2013257992A

  • Cathode active material for battery, and battery using cathode active material

    JP2018085324A

  • Solid electrolytic composition, electrode sheet for full-solid secondary batteries, full-solid secondary battery, and method for manufacturing electrode sheet for full-solid secondary batteries and full-solid secondary battery

    WO2017141735A1

  • Solid electrolyte material, and cell

    WO2018025582A1